OPTIMALISASI PENGGUNAAN SISTEM CREW ROTATION TERHADAP BIAYA PENERBANGAN CARTER PT GARUDA INDONESIA - Mustika Sari; Rizky Jamiatun Muslimah; Devi Marlita (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
PT. Garuda Indonesia (Persero) Tbk is a state-owned company that engaged in air transport service.  The main issue discussed in this research is the relation between charter flight costs to crew rotation practiced in PT. Garuda Indonesia (Persero) Tbk in flight route Jinan – Denpasar based on an agreement with Royal-Sino Energy Aviation.  The objective of this research is to find out the influence of charter flight cost by crew rotation.  Data were analyzed using descriptive explorative.  Based on the result of the analysis, it is revealed that PT. Garuda Indonesia (Persero) Tbk uses crew pairing system in its applied crew rotation, but it is not fully optimized.  The crew pairing and crew scheduling optimization can be applied in PT. Garuda Indonesia (Persero) Tbk so that the crew cost expenses can be reduced thus giving bigger margin to the company.